Research of the current state of the market of vitamin and mineral complexes for pregnant women and information support for women during pregnancy - V. O. Demchenko; N. O. Tkachenko; V. O. Demchenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim of the work is to study of the domestic market of vitamin and mineral complexes for pregnant women with the subsequent formation of an information array for making rational decisions on the formation of the pharmacy range of this group of products and information support for women during pregnancy.